2016
DOI: 10.18632/oncotarget.13552
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 deteriorates Fabry cardiomyopathy and contributes to the development of left ventricular hypertrophy in Fabry patients with GLA IVS4+919 G>A mutation

Abstract: RationaleA high incidence of GLA IVS4+919 G>A mutation in patients with Fabry disease of the later-onset cardiac phenotype, has been reported in Taiwan. However, suitable biomarkers or potential therapeutic surrogates for Fabry cardiomyopathy (FC) in such patients under enzyme replacement treatment (ERT) remain unknown.ObjectiveUsing FC patients carrying IVS4+919 G>A mutation, we constructed an induced pluripotent stem cell (iPSC)-based disease model to investigate the pathogenetic biomarkers and potential the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
3
19
1
Order By: Relevance
“…After the cardiac differentiation, these differentiated cardiomyocytes (FC-iPSC-CMs) all exhibited CM-like phenotypes ( Figure 2 A) and the expression of cardiac-specific markers, including α-actinin and MYL2, at post-induction 30 days ( Figure 2 B). Comparing with Ctrl-iPSC-CMs, the microscopic examination of all FC-iPSC-CMs revealed remarkable cellular hypertrophy, as described previously [ 31 , 32 ]. Moreover, during differentiation, the mRNA and protein expression levels of GLA ( Figure 2 C,D), as well as the enzyme activity of GLA ( Figure 2 E), were all declined and reached the maximal decrease at day 60 post-induction.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…After the cardiac differentiation, these differentiated cardiomyocytes (FC-iPSC-CMs) all exhibited CM-like phenotypes ( Figure 2 A) and the expression of cardiac-specific markers, including α-actinin and MYL2, at post-induction 30 days ( Figure 2 B). Comparing with Ctrl-iPSC-CMs, the microscopic examination of all FC-iPSC-CMs revealed remarkable cellular hypertrophy, as described previously [ 31 , 32 ]. Moreover, during differentiation, the mRNA and protein expression levels of GLA ( Figure 2 C,D), as well as the enzyme activity of GLA ( Figure 2 E), were all declined and reached the maximal decrease at day 60 post-induction.…”
Section: Resultssupporting
confidence: 83%
“…In Taiwan Fabry cohorts with high incidence of IVS4+919 G>A mutation and later-onset cardiac phenotype, the mechanisms that contribute to development of FC in such cardiac variant remained poorly understood. We previously demonstrated that neutralization of interleukin-18 effectively ameliorated the cardiomyocyte hypertrophy in FC-iPSC-CMs from Fabry patients with IVS4+919 G>A mutation [ 32 ]. Chou et al further reported that conventional ERT did not modify the impaired energy utilization in FC-iPSC-CMs carrying IVS4+919 G>A mutation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many GLA splicing mutations have also been described in case reports, but only the deep intronic mutation c.639 + 919 G > A was well studied (Ishii et al, 2002; Chien et al, 2016; Palhais et al, 2016; Chang et al, 2017; Chiang et al, 2017). In the present study, we identified a novel splicing mutation in a FD patient in which the first nucleotide of GLA intron 5 is changed from G to A.…”
Section: Introductionmentioning
confidence: 99%
“…All patients with FD in our study were patients with a known intronic mutation, IVS4 + 919G > A. This mutation is documented to have a high frequency in Taiwan and mainland Chinese populations and has been linked to late-onset FD [38][39][40][41]. Up to 80% of FD incidence in Taiwan can be accounted for by this specific mutation.…”
Section: Plos Onementioning
confidence: 88%